2017
DOI: 10.2147/copd.s130925
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of quality of life is associated with the exacerbation frequency in individuals with alpha-1-antitrypsin deficiency – analysis from the German Registry

Abstract: BackgroundAlpha-1-antitrypsin deficiency (AATD) is a rare hereditary disease that is associated with a higher risk to develop chronic obstructive pulmonary disease and liver cirrhosis. Previous cross-sectional studies on AATD individuals have shown a relationship between worse St George’s Respiratory Questionnaire (SGRQ) scores and elevated exacerbation rate or high cigarette consumption. There is a lack of longitudinal data on the relationship between the exacerbation rate and worsening of SGRQ during disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The difference likely reflects a combination of the centralisation of patient care and the degree of monitoring carried out at our centre as well as potential improvements in patient care over the intervening 14 years. More recently a study from Germany [ 26 ] also documented a slow decline in SGRQ in AATD (+ 1.2 units for total score) which weakly reflected annual exacerbation rates [ 26 ]. However, that data was self-reported and included unquantified patients with the SZ phenotype and a significant proportion on augmentation therapy, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…The difference likely reflects a combination of the centralisation of patient care and the degree of monitoring carried out at our centre as well as potential improvements in patient care over the intervening 14 years. More recently a study from Germany [ 26 ] also documented a slow decline in SGRQ in AATD (+ 1.2 units for total score) which weakly reflected annual exacerbation rates [ 26 ]. However, that data was self-reported and included unquantified patients with the SZ phenotype and a significant proportion on augmentation therapy, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Our review suggests that patients with AATD who have frequent exacerbations (⩾3 per year) or chronic sputum expectoration have a poorer QoL than patients without [74], and that SGRQ scores may be significantly correlated with both exacerbations and dyspnoea [76]. Exacerbations are often associated with long-term sequelae including significant, permanent loss of lung function [26,129,130]. However, exacerbations are random events that are driven by infections and outcomes can vary substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that patients with frequent exacerbations had a significantly lower QOL than patients with less frequent exacerbations 63 . Bernhard et al 64 reported that changes in HRQOL were more dependent on the frequency of exacerbation than on FEV1 and DLCO decline. Hospitalization also increased the financial burden and reduced QOL 65 .…”
Section: Discussionmentioning
confidence: 99%